Setting Relay Diferensial Siemens 7UT5121 pada Transformator dengan ETAP untuk Meningkatkan Sistem Proteksi - Dimas Nur Prakoso; Yuli Prasetyo; Budi Triyono; Basuki Winarno (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2026)
The development of the electric power system is quite rapid in Indonesia, where the development of the electric power system will not experience a decline and will continue to increase. To distribute electrical energy to consumers, transformers are the main component in the electrical system. During its operation, transformers often experience faults, making reliable protection and security systems necessary to maintain the smooth operation of the system. Protection systems are designed to interrupt faulty currents and protect equipment from damage caused by these currents. One of the primary protection devices for transformers is the differential relay, which operates quickly without requiring coordination with other relays. Differential relays work based on the vector difference between two or more electrical quantities exceeding a predetermined threshold. In this study, a Siemens 7UT5121 protection relay was used. To facilitate testing and fault analysis in the settings of this protection relay, simulations were conducted using ETAP software. The protection relay settings were configured to safeguard the transformer if there was a current difference between the CT on the primary and secondary sides within the protection zone. Based on calculations, the CT ratio for nominal current (I₁) was found to be 230.94 A, and the nominal current (I₂) was 1905.25 A. The CT secondary currents were calculated as 0.769 A for I₁ and 0.866 A for I₂. In the differential relay, the differential current was recorded at 0.097 A, while the restrain current was 0.817 A. The slope percentage analysis yielded values of 11.18% for slope 1 and 23.74% for slope 2. The differential current setting value obtained was 0.379 A. The relay will not operate if a fault occurs outside the protection zone, ensuring the reliability of the transformer protection system